496 Do Patients and Healthcare Providers Have Similar Perceptions of Available Narcolepsy Educational Materials and Treatment Options?. (3rd May 2021) - Patterson, Mark
Abstract: Introduction: Studies have shown that patients typically retain <50% of the information communicated to them by their healthcare providers. This lack of retention can lead to serious problems and misunderstandings regarding the condition, its treatment, and course. The goal of this study was to compare the information sleep specialists report providing to patients with the materials narcolepsy patients recall receiving. Methods: Deidentified on-line surveys were submitted to active members of the American Academy of Sleep Medicine and to patients with narcolepsy Type 1 (NT1) and Type 2 (NT2) via the cloud-based software service company SurveyMonkey. These patients were recruited from the private Facebook group 'Doctors and Narcoleptic Patients'. Results: Results were received from a total of 75 patients (68% NT1, 29% NT2, 3% uncertain type; mean time since diagnosis: 11 years) and 18 sleep specialists (mean time in practice: 22 years). Physicians reported that their practices provided written material about narcolepsy to patients 69% of the time. By contrast, only 32% of patients recall receiving written information. Regarding treatment options, the groups reported variable results, with 94% of doctors/86% of patients discussing modafinil/armodafinil, 89% of providers/68% of patients communicating about amphetamines/methylphenidate, and 83% of physicians/47% of patients considering sodium oxybate. Additionally, only 56% of physicians were aware of narcolepsy patient advocacy organizations. Conclusion: With the ready availability of social media and the exchange of oft inaccurate medical information, it is essential that physicians supply their patients with accurate up-to-date materials, especially following the diagnosis of a life-altering condition such as narcolepsy. This study suggests that there is a mismatch between the information which physicians believe they are providing and the materials the patients recall receiving. In addition to the medical care sleep specialists provide, patients and their families frequently rely on support from condition-specific organizations. Health care providers should be aware of the local and national organizations and supply their patients with contact information in an effort to provide a more holistic approach to medical care. Efforts are necessary to educate physicians about their patients' needs for on-going care, distinct from that provided solely in the clinical setting. Support (if any):